JMDE - Five Years in Review - Margaret M. Richardson (The Evaluation Center at Western Michigan University, 2008)
2008 marks the fifth year of publication for JMDE. The growth of JMDE, whether measured in terms of readership or in the evolution of ideas, reflects the increasing importance of evaluation, not as a separate process, but more as the development of an evaluative state of mind. Just in terms of readership, at the milestone 5th issue, JMDE had over 1750 "committed readers"-those who requested notification of publication of new issues, the website had over 19,000 hits according to our own measure, but up to 30,000 per day according to independent estimates by Lars Balzar.